Upaya Penurunan Tingkat Perilaku Agresif Di Madrasah Dengan Teknik Konseling Kelompok (Studi Kasus Pelanggaran Disiplin Aturan Madrasah ) Pada Siswa Klas 7 F Semester Genap Tahun Pelajaran 2016/ 2017 Mtsn Prambanan Kabupaten Klaten - Sri Hartini (Universitas Alma Ata, 2017)
The formulation of this research problem is, Is using group counseling technique technique can decrease aggressive behavior in grade VII student MTs N Prambanan academic year 2016/2017 semester II? The research is done by using qualitative approach, that is kind of research of class action. Stages of research conducted according to the stages proposed by Kemmis and Mc Taggart Subject researchers amounted to 30 students. The results showed that Behavior of aggressive attitude of 7F grade students through group counseling service on cycle I 50% for aggressive behavior of male students and 10% for female students so as to decrease aggressive behavior of fight in school 96.6% to 36.6% 29 students behave aggressively in two weeks reduced to 18 learners. With the decrease in the number of students as many as 11 students, then in cycle II of 96.6% decreased again to 10%, which means there is a change of 86.6% is a significant decline. This suggests that through the provision of group counseling services may decrease aggressive fighting behavior in schools at 7 7th grade students MTsN Prambanan Klaten District.